“ANGSA BIMO” (ANGKRINGAN SADAR HOBI MACA) CULTIVATE LITERACY CULTURE THROUGH METHOD CONTEST “ORTU NGACA” (CONTEST ORIGAMI, WRITE, RECITE, READ) ON STUDENT ELEMENTARY SCHOOL MENOREH SALAMAN - Darwiastuti, Betty Risma; Sari, Suci Wulan; Mayawati, Annis Ika; Yunanto, Alif Rizki; Oktafianjati, Chabib; Istiningsih, Galih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The low reading culture at SDN Menoreh Salaman is supported by several factors, among others, the management of poorly organized libraries, which causes the decreasing interest in reading children. The purpose of this activity is to improve the literacy culture of school residents and improve the library system so that it becomes a place that is comfortable and operates in accordance with its function. The method used is ANGSA BIMO (angkringan sadar hobi maca) which is the innovation of angkringan-shaped library that is made to attract the attention of the school to visit and read (various books provided), the concept of ANGSA BIMO in combination with CONTEST ORTU NGACA method which in its presentation is implemented in learning process by developing the creativity of each child through Contest origami, write, ngaji, and maca. The results obtained from applying ANGSA BIMO method combined with CONTEST ORTU NGACA is the recognition of culture of literacy and the emergence of reading interest for the citizens of the school, the emergence of the spirit to read the citizens of the school.